Strategi Percepatan Pembangunan Desa Berkembang: Upaya Menuju Desa Mandiri yang Berkelanjutan - Nuri Aliyani (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The aim of this study is to determine the strategy for accelerating the development of Developing Villages towards a sustainable Independent Village, through PESTEL-SOAR analysis and case study of Pondok Udik Village. The success of village development in Indonesia is seen from the status of the village through the Village Build Index. Developing Villages are the center of attention because the number of villages included in the Developing Village category is 57.01% in 2020, thus requiring accelerated development to become developed and independent villages. The research is use descriptive-qualitative research methods. The types of data consist of primary data obtained through interviews and observations, and secondary data. The results of the study indicate that there is a strategy for accelerating development towards a sustainable Independent Village. The strategies that can be carried out are: first, the S-A strategy that utilizes village strengths to realize the aspirations of all local village communities, focusing on the economic, social, and village infrastructure fields. Second, the S-R strategy, which utilizes the strength of the village to realize the village's vision and mission, focuses on exploiting the potential of the village. Third, the O-A strategy that takes advantage of existing opportunities to realize the aspirations of the village community, focusing on the social sector of the village community and village infrastructure. Fourth, the O-R strategy that takes advantage of existing opportunities to realize the village's vision and mission, focusing on sustainable village development. Abstrak. Tujuan dari penelitian ini adalah untuk menentukan strategi untuk mempercepat pembangunan desa berkembang menuju sebuah desa independen yang berkelanjutan, melalui analisis PESTEL-melambung dan studi kasus Desa Pondok Udik. Keberhasilan pembangunan desa di Indonesia terlihat dari status desa melalui Indeks Pembangunan Desa. Membangun desa-desa adalah pusat perhatian karena jumlah desa termasuk dalam kategori berkembang Desa adalah 57.01% pada tahun 2020, sehingga membutuhkan pembangunan menjadi berkembang dan desa independen. Penelitian ini menggunakan metode penelitian deskriptif. Jenis data terdiri dari data primer yang diperoleh melalui wawancara dan pengamatan, dan data sekunder. Hasil penelitian menunjukkan bahwa ada strategi untuk mempercepat pembangunan menuju sebuah desa independen yang berkelanjutan. Strategi yang dapat dilakukan adalah: pertama, strategi yang memanfaatkan kekuatan desa untuk mewujudkan aspirasi komunitas desa, fokus pada ekonomi, sosial, dan bidang infrastruktur desa. Kedua, strategi S-R, yang memanfaatkan kekuatan desa untuk menyadari visi Desa dan misi, berfokus pada mengeksploitasi potensi desa. Ketiga, strategi yang mengambil keuntungan dari kesempatan yang ada untuk mewujudkan aspirasi masyarakat desa, berfokus pada sektor sosial dari komunitas desa dan infrastruktur. Keempat, strategi O-R yang mengambil keuntungan dari peluang yang ada untuk menyadari visi dan Misi Desa, fokus pada pembangunan desa yang berkelanjutan.